2014
DOI: 10.1038/ejhg.2014.56
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis demonstrates the highly polygenic character of age-related hearing impairment

Abstract: We performed a genome-wide association study (GWAS) to identify the genes responsible for age-related hearing impairment (ARHI), the most common form of hearing impairment in the elderly. Analysis of common variants, with and without adjustment for stratification and environmental covariates, rare variants and interactions, as well as gene-set enrichment analysis, showed no variants with genome-wide significance. No evidence for replication of any previously reported genes was found. A study of the genetic arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 18 publications
4
96
0
1
Order By: Relevance
“…More than 100 loci were identified in familial studies of nonsyndromic hearing loss, with ~30% of the studies failing to identify the specific gene or mutation implicated (http://hereditaryhearingloss.org/). The genetic basis for the more common and complex forms of hearing and balance disorders, such as presbycusis and disequilibrium and falls in the elderly, has been established (Fransen et al, 2014) but remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…More than 100 loci were identified in familial studies of nonsyndromic hearing loss, with ~30% of the studies failing to identify the specific gene or mutation implicated (http://hereditaryhearingloss.org/). The genetic basis for the more common and complex forms of hearing and balance disorders, such as presbycusis and disequilibrium and falls in the elderly, has been established (Fransen et al, 2014) but remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the genes and processes involved in the maintenance of hearing in adults will similarly lead to an even greater understanding. However, it is likely that multiple pathways interact through positive and negative feedback loops to maintain auditory function [4]. Human genetic diversity, combined with the various experiences of the human condition, may obscure the roles of individual genes and pathways in large scale human studies [4].…”
Section: Discussionmentioning
confidence: 99%
“…For example, hearing loss may develop after exposure to prolonged and excessive noise [2] or to ototoxic drugs such as aminoglycosides [3]. Each individual likely has genetic variation in their susceptibility to these insults [4]. Over a hundred genes that affect hearing loss during development have been identified [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth GWA study was undertaken into the hearing status of 3,614 individuals (all aged 44-45 years) in the British 1958 Birth Cohort and again failed to find a significant association but provided the basis for the subsequent characterisation of a novel hearing gene, ESRRG, in a knock-out mouse model [13]. The fifth by Fransen et al [14] is an extension of the first GWA study, employing a larger sample set. This recent study revealed no significant GWAs for ARHL and also did not add support to any of the previously reported associations in GRM7 or GRM8 .…”
Section: The Need For An Animal Modelmentioning
confidence: 99%